The development and evaluation of a cohesion-building programme for a South African male collegiate basketball team - Razafimbola, Sandimampita (Rhodes University, Faculty of Humanities, Department of Psychology, 2008)
There is a general consensus among sport coaches and practitioners that it is better to work with a cohesive team. Research on cohesion has provided positive links between cohesion and performance as well as the overall well-being of the team and its members. The purpose of this study is to develop and evaluate a cohesion-building programme under an Action Research paradigm. The Group Environment Questionnaire, in parallel with focus group discussions were used to assist in the development and evaluation of a cohesion-building programme tailored to the specific needs of the Rhodes University men's basketball 1st team. The team is known to be a good team but it was missing something that made it become great. Fostering higher cohesiveness was deemed to be the missing link to the chain of success. Various changes were brought to the 1) team structure, 2) team processes, 3) team environment to enhance the team's cohesiveness levels. It was found that the programme was positive and powerful in that it accelerated the process of cohesion building within the team. It was also found that the programme had the power to transcend demographical barriers and unite people from diverse backgrounds. Finally, the programme increased the team's performance level and enabled it to achieve objectives that were never achieved by any other men's basketball team at Rhodes University before. Naturally there are going to be some ups and downs, especially if you have individuals trying to achieve at a high level. But when we stepped in between the lines, we knew what we were capable of doing. When a pressure situation presented itself, we were plugged into one another like a cohesive unit. That's why we were able to come back so often and win so many close games. And that's why we were able to beat more talented team. - Michael Jordan (former Chicago Bulls; NBA Hall of Famer).
Keywords: Teamwork (Sports); Basketball teams; College sports; Sports -- Psychological aspects